Exercise responses after altitude acclimatization are retained during reintroduction to altitude - Beidleman, B. A.; Muza, S. R.; Rock, P. B.; Fulco, C. S.; Lyons, T. P.; Hoyt, R. W.; Cymerman, A. (Medicine & Science in Sports & Exercise, 1997)
owing altitude acclimatization, ventilation is increased and heart rate, plasma volume, and lactate accumulation are decreased during submaximal exercise. Males (N = 6) were evaluated on physiological parameters during an exhaustive exercise bout at introduction to altitude, after 16 days of acclimatization, after 8 days at sea level, and upon reintroduction to altitude. It was found that the adaptations that occurred during the first adaptation were retained in significant but partial amounts after the 8-day sea level intervention. [The tenor of the paper suggests that the retention is total.] Implication: Altitude adaptations deteriorate slowly upon return to seal level. If the return-duration is sufficiently short, significant proportions of the acclimated features will be retained and will make subsequent adaptations both faster and easier.